Przekraczanie tradycji przyznawania człowiekowi uprzywilejowanej pozycji wobec zwierząt w aktach uobecniania indyferencji - Orlik, Piotr (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
The traditional view on the fact that animals have a lower status than humans were consolidated, among others, in the writings of Aristotle and Descartes. The traditional differences can, however, be questioned in the acts that are called by the author "the acts of anticipation of indifference”. In the following article two such acts of transcending the tradition of granting humans a privileged status in comparison to animals are indicated and analyzed: (1) in A treatise of human nature by David Hume and (2) in the philosophy of the ancient skeptic – Aenesidemus.